High-voltage measurements on the 5 ppm relative uncertainty level with collinear laser spectroscopy. (28th February 2018) - Krämer, J; König, K; Geppert, Ch; Imgram, P; Maaß, B; Meisner, J; Otten, E W; Passon, S; Ratajczyk, T; Ullmann, J; Nörtershäuser, W
Abstract: We present the results of high-voltage collinear laser spectroscopy measurements on the 5 ppm relative uncertainty level using a pump and probe scheme at the 4 s 2 S 1 / 2 → 4 p 2 P 3 / 2 transition of 40 C a + involving the 3 d 2 D 5 / 2 metastable state. With two-stage laser interaction and a reference measurement we can eliminate systematic effects such as differences in the contact potentials due to different electrode materials and thermoelectric voltages, and the unknown starting potential of the ions in the ion source. Voltage measurements were performed between  −5 kV and  −19 kV and parallel measurements with stable high-voltage dividers calibrated to 5 ppm relative uncertainty were used as a reference. Our measurements are compatible with the uncertainty limits of the high-voltage dividers and demonstrate an unprecedented (factor of 20) increase in the precision of direct laser-based high-voltage measurements.